Implementasi Klasifikasi Tipe Dasar Telekesehatan pada Rumah Sakit - TANAZZA, Syi'ar Aprilla; Sari, Ni Putu Desy Purnama; Prastowo, Bayu (Politeknik Baubau, 2024)
Remote health facility services in Indonesia are regulated by government and health association policies. The service is defined as telemedicine to facilitate information, communication and clinical systems for individual or group health. The implementation of the telehealth system is contained in the Minister of Health Regulation number 20 of 2019. The readiness of this policy provides a positive value in the hospital environment to maximize service delivery. However, is this government support related to the implementation of the telehealth system in the hospital environment? This study does not analyze the telehealth system in a complex manner, but the basis of telehealth following standard protocols of the Indian Medical Council. The standard basis for telehealth protocols in the form of textual characteristics is converted into numerical values by modifying the Likert scale. The assessment is based on observing the conformity of the standards with the telehealth media used in each hospital. The hospitals that are the research sample are those listed in the hospital accreditation commission data set. The suitability value is analyzed using a partial least square. Data processing shows that the average variance extracted, composite reliability and Cronbach's alpha values are in the range of 0.8 to 1.0, the correlation value between indicators is ≥0.06 and the R2 value is 1.0. These values indicate that the basic characteristics of telehealth used as indicators have discriminant validity, high reliability and reliability in the formulation of hypotheses. These indicators have a positive relationship to the construct and form a strong structural model.